(untitled) (Annals of Medical Research, 2024)
Aim: This study was carried out to determine the factors affecting the health and social lives of individuals with Type I diabetes. Materials and Methods: The sample of the study consisted of 14 individuals with Type I diabetes living in Istanbul province. The quantitative data of the study were collected using a personal information form, and the qualitative data were collected through two open-ended questions. Results: Content analysis was used to evaluate qualitative data. The mean age of the individuals with Type I diabetes was 36.1% (n=14) years. As a result of the content analysis, two main themes and eight sub-themes were determined. Accordingly, the themes were negative emotions towards the illness and fear of being unable to maintain health during the pandemic process. Conclusion: In this study, individuals with Type I diabetes were found to have negative thoughts and to experience anxiety and fear about their health due to the COVID-19 pandemic. During the pandemic process, they were particularly affected by the inability to exercise enough and the deprivation of social life. In line with these results, the study revealed that the mental and physical needs of individuals with Type I diabetes, which is a disadvantaged group during the pandemic process. In these cases, it is recommended to develop teams that will provide support for remote chronic disease monitoring of individuals with type 1 diabetes, to train health professionals, to provide multidisciplinary support to individuals by investing in these issues, and to create emergency action plans that include all elements.